Handbook of Leaving Religion - Enstedt, Daniel; Larsson, Göran; Mantsinen, Teemu T. (Brill Handbooks on Contemporary Religion, 2019)
The Handbook of Leaving Religion introduces a neglected field of research with the aim to outline previous and contemporary research, and suggest how the topic of leaving religion should be studied in the future. Readership: All interested in conversion, deconversion and apostasy processes, and anyone concerned with methodological and theoretical questions related to leaving or changing religion.